A review on catalyst formulation, reaction condition and reaction mechanism for dry reforming of methane/biogas to syngas - Abdul Hadi, Abdullah; Ahmad Zamani, Ab Halim; Amri, Mohamed (Zibeline International Publishing, 2023)
Syngas production using methane dry reforming is a promising method that needs more exploration due to the benefits of harnessing the two most dangerous greenhouse gases, carbon dioxide and methane. The process can also employ biogas as a feed gas, which has a methane-to-carbon dioxide ratio of 1.5. However, due to the highly endothermic nature of the dry reforming reaction, a large quantity of energy is required. It has been demonstrated that the catalyst can be applied to lower the energy barrier and hence lower the reaction temperature. Many researchers have studied catalysts for dry reforming of methane. Coke deposition and active metals sintering are two conditions that can affect catalyst effectiveness. Many studies have claimed that the manipulated variables must be regulated in order to obtain an optimum catalyst for methane dry reforming. The impact of variables on catalyst performance was highlighted and thoroughly examined in this paper. The variables were separated into two groups: catalyst formulation variables and dry reforming reaction operating variables. Furthermore, this paper examined the potential of response surface methodology as techniques for determining the optimal variables with the fewest number of experiments and least expensive. This study also explored the reaction mechanism of dry reforming of methane over catalyst in order to get a better understanding of the essential path that the reaction takes.